2019
DOI: 10.1108/ijif-04-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the intention to adopt Islamic banking in a non-Islamic developing country

Abstract: Purpose This paper aims to investigate the contribution of attitude, subjective norm and religiosity on the intention to adopt Islamic banking in an emerging economy like Uganda, which is a secular state that is in the early stages of adopting Islamic banking. Design/methodology/approach This study uses a cross-sectional and correlational research design. Usable questionnaires were received from 258 managers of their own micro businesses. A hierarchical regression analysis was used to test the hypotheses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 26 publications
10
78
1
Order By: Relevance
“…In this study, religiosity has a positive and significant effect on halal cosmetics purchase intentions. The results of this study are in line with previous studies that high and low religiosity will affect individual intentions [13].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, religiosity has a positive and significant effect on halal cosmetics purchase intentions. The results of this study are in line with previous studies that high and low religiosity will affect individual intentions [13].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the attitude has a positive and significant effect on halal cosmetics purchase intention. The results of this study are in line with previous studies that the attitude of an individual on a product will affect the purchase intention of the product [13], [27], [28]. The results of this study explained that the more positive the consumer's attitude towards halalcertified products, the greater the intention to purchase the product.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many researchers have found a positive and significant effect of religiosity on saving interest in Islamic banks (Afiah, 2016;Andriani, 2015;Rahmanto, 2016;Shofwa, 2017). The results of the research by Bananuka, Kaawaase, Kasera, & Nalukenge (2019) also show that religiosity is a significant determinant for the adoption of Islamic banking in non-Islamic developing countries (Uganda). Suhartanto (2019) found a significant effect of religiosity on intention toward Islamic banks.…”
Section: Introductionmentioning
confidence: 87%
“…Andriani 2015, Rahmanto (2016), and Afiah (2016) succeeded in proving the significant influence of religiosity on saving interest in Islamic banks. Shofwa (2017) and (Bananuka, Kaawaase, et al, 2019) also found the effect of religiosity on the decision of customers of savings products at Bank Syariah Mandiri. The results of the factor analysis show the significant influence of religiosity on the main preference for saving on Islamic banking (Lestari, 2016).…”
Section: Research Hypotheses Developmentmentioning
confidence: 96%